The hero’s problem in the autobiographical novel «I do not feel sorry for I. Shchegolikhin, I do not call, I do not pay...» (Eurasian Journal of Philology Science and Education, 2018)
In article the hero’s problem in the autobiographical novel of the Russian writer of Kazakhstan Ivan Pavlovich Shchegolikhin is considered, autobiographical data on the writer’s life are stated. The author pays special attention to an autobiographical genre in which reminiscence and memoirs are transferred. In article the author gives information on all autobiographical works of the writer which he addressed in recent years. The author considers the novel «I Am Not Sorry, I Do Not Call, I Do Not Pay...» as the main object the analysis and describes the idea of its creation which was prompted most life. According to the author, in the novel prevailing the thought that the author-hero, despite all difficulties which fell to his lot despite sharp feeling of total tragic element of the life surrounding it, remained is it is faithful to the idea of morality and justice, and in it sees the appointment on the earth. Strictly thought over three-part composition of the novel and the fact that in each of them – the dynamic plot intertwines with monologues thoughts is described. According to the author the novel is based on a historico-philosophical plot. The author states questions of how the writer in the novel argues on the premilitary childhood, on growing torments, on the first love, on tests by accident war, on losses of relatives and friends, on pain and bitterness of treachery. The hero narrates – the constructed image of the person passing the course of life. For comparison with different positions, are presented in article examples of other autobiographical novels.Also, article contains a large number of examples and quantitative data the illustrating and confirmingbasic provisions of article.